Photoelectrocatalytic degradation of 17α-ethinylestradiol and estrone under UV and visible light using nanotubular oxide arrays grown on Ti-0.5wt%W - Escudeiro de Oliveira, Marizilda; Barroso, Bruno Lupi; de Almeida, Juliana [UNESP]; Moraes, Maria Lourdes Leite; de Arruda Rodrigues, Christiane [UNESP] (Elsevier, 2020)
Environmental concern with emerging contaminants has increased in recent years, especially with regard to endocrine-disrupting compounds (EDCs), among them hormones. Conventional water treatment processes have been shown to be ineffective in removing these compounds from water and sewage, while heterogeneous photocatalysis has been demonstrated to be a promising technique. However, the catalytic efficiency is strongly related to the choice of the photocatalyst material. In order to obtain a fast and efficient degradation of these endocrine disruptors, nanotubes grown on Ti-0.5wt%W alloy (NT/Ti-0.5W) were used in photocatalytic (PC) and photoelectrocatalytic (PEC) processes for the degradation of estrone (E1) and 17α-ethinylestradiol (EE2) under irradiation with ultraviolet (UV) and visible light. The NT/Ti-0.5W catalysts were synthesized by an anodization process, followed by thermal treatment at 450 °C. Raman, X-ray diffraction and diffuse reflectance spectroscopic analyses indicated that the tungsten doping process had modified the nanotubular TiO2. The doped samples exhibited superior photoactivity compared to un-doped samples and other semiconductors under UV and visible irradiation due to a reduction in the rate of recombination of photogenerated charges and the displacement of the flat-band potential to more negative values. Higher values of the degradation rate constant were found for both hormones in the PEC process using NT/Ti-0.5W under UV radiation; the percentage removals of EE2 and E1 were 66% and 53.4%, respectively, after only 2 min of treatment. With visible light, 1.8 min and 4.6 h were required for the removal of 50% of E1 and EE2, respectively. The degradation of E1 could be fit with a zero-order kinetic model, while a first-order kinetic model was required for EE2 degradation. Degradation routes were suggested for E1 and EE2. The results demonstrate that the combined use of NT/Ti-0.5W and the PEC process provides excellent performance for the degradation of emerging contaminants in wastewater when compared to a NT/TiO2 electrode.
Keywords: 17α-ethinylestradiol; Emerging contaminants; Estrone; Photodegradation pathways; Photoelectrocatalysis; W-doped TiO2 nanotubes